Echo Park : Harry Bosch #12 - Connelly, Michael, 1956-; Cariou, Len (New York : Hachette Audio, 2006)
In 1993 Marie Gesto disappeared after walking out of a supermarket. Harry Bosch worked the case but couldn't crack it, and the twenty-two-year-old was never found. Now, more than a decade later, with the Gesto file still on his desk, Bosch gets a call from the District Attorney. A man accused of two heinous murders is willing to come clean about several others, including the killing of Marie Gesto. Taking the confession of the man he has sought--and hated--for thirteen years is bad enough. Discovering that he missed a clue back in 1993 that could have stopped nine other murders may just be the straw that breaks Harry Bosch.
In container (17 cm.).
Title from container.
"Unabridged"--Container.
"Fiction"--Container.
Compact disc.
Read by Len Cariou.
Keywords: Bosch, Harry (Fictitious character) -- Fiction; Police -- California -- Los Angeles -- Fiction; Missing persons -- Fiction; Young women -- Crimes against -- Fiction; Cold cases (Criminal investigation) -- Fiction; Serial murderers -- Fiction; Audiobooks; Detective and mystery stories; Detective fiction; Mystery fiction